Main bacterial agents associated with antimicrobial resistance in the treatment of Urinary Tract Infections (UTI) in female patients (Research, Society and Development, 2021)
Known as one of the most common bacterial infections in humans, the urinary tract infection (UTI), mainly affects women. It is a very common pathology in the population, responsible for a large number of medical consultations and hospitalizations, resulting in serious public health problems. This represents a common cause of prescription drugs for its treatment, such as antibiotics, which, when done improperly, can be related to the growing emergence of bacterial resistance. The aim of this study was to conduct a literature review on the main bacterial agents associated with antimicrobial resistance in the treatment of urinary tract infections (UTI) in female patients. As for the methodological aspects, the study is an integrative literature review, from 2015 to 2021, based on databases such as Scientific Electronic Library, Lilacs (Scielo) Latin American and Caribbean Literature on Health Sciences (Lilacs) through the Virtual Health Library (VHL) platform, PubMed Medline data and other physical sources. The results show that: 1) the correct use and proper guidance on antibiotics are very important; 2) the awareness of professionals and the population about the rational use, especially broad-spectrum antibiotics, such as quinolones, reducing the pressure on the choice of antibiotics; 3) it is necessary to understand bacterial resistance in outpatient clinics and hospitalized with UTI, as it is important to monitor the actions of resistance and avoid prescriptions that do not have an antimicrobial spectrum.